Avaliação da outer membrane protein A de rickettsia rickettsii em enzyme-linked immunosorbent assay para o diagnóstico diferencial de riquetsioses - Muniz, Ana Paula Mendes (2021)
In Brazil, the disease cause by Rickettsia rickettsii in humans is the main tick-borne zoonosis and has a high lethality rate, while Rickettsia parkeri is responsible for a milder disease. Currently, the gold standard assay for the diagnosis of Rickettsia infection is the immunofluorescence assay (IFA), which has some disadvantages, such as the preparation of the antigen by growing the Rickettsia strains used in IFA in mammalian (Vero) cell culture and well-trained personnel to carry out the test. This study aimed to evaluate two synthetic peptides, named OmpA-pLMC and OmpA-RRS, and a recombinant protein corresponding to segments of the outer membrane protein A (OmpA), which is present in Rickettsia species of the spotted fever group (SFG), as antigens in Enzyme-linked immunosorbent assay (ELISA) for the diagnosis of rickettsial infections. For this, serum samples of capybara (Hydrochoerus hydrochaeris), horse (Equus caballus), and opossum (Didelphis albiventris) that were reactive or non-reactive by IFA were used. The amino acid sequences of the synthetic peptides were selected by using B Cell Epitope and Epitopia and OmpA sequences of R. rickettsii strain Brazil and R. parkeri strain Maculatum and Portsmouth. With OmpA-pLMC, a peptide with amino acid sequence common to both Rickettsia species, there were no significant differences in average reactivity (with ELISA DO values) between IFA-positive and IFA-negative sample groups of capybara (p = 0.1184) and horse (p = 0.1836). On the other hand, with opossum samples a significant difference between IFA-positive and IFA-negative groups (p = 0.0142; AUC 0.8857) was observed. With OmpA-pRRS, a peptide that has an amino acid sequence identical to the OmpA sequence of R. rickettsii, there was significant difference between the groups IFA-positive for R. rickettsii and IFA-negative (p = 0.0476, ASC = 0.7537), but not between IFA-positive for R. parkeri and IFA-negative (p = 0.7527). For opossum serum samples, there was a significant difference between the IFA-positive and IFA-negative groups (p = 0.0040, ASC = 0.9467). With the recombinant OmpA, which was obtained in bacterial expression system, there was a significant difference between the IFA-positive and IFA-negative groups only with opossum samples (p = 0.0465, ASC = 0.8143). Therefore, at least to opossums, OmpA-pLMC, OmpA-pRRS, and recombinant OmpA demonstrated potential to be used as antigens for immunodiagnostic assays to detect R. rickettsii infections, and probably to R. parkeri and other species of the SFG. Peptide OmpA-pRRS was also shown to be a potential antigen for immunodiagnostic assays to detect of R. rickettsii infections in horses.